Determinan Tingkat Kesejahteraan Buruh Jagung Di Kabupaten Sumbawa Dalam Perspektif Hukum Fikih - Mili Hariyanti; Linda Destia Putri; Alan Budi Kusuma (Jurnal ini dipublikasikan oleh Pusat Penelitian dan Pengabdian Publikasi (P3M) STAI Nahdlatul Watan Samawa-licensed under a Creative Commons Attribution-ShareAlike 4.0 International License., 2024)
This researgh aims to describe or describe the reality of whether the welfare of corn workers in Sumbawa Regency is consideret in accordance with Islamic teachings and Islamic jurisprudence laws in Sumbawa regenvcy. The research used in this research is qualitative, the walfare of corn workers in Sumbawa district is assessed from several aspects such as safe working conditions, decent wages, access to edicationand health, and protection’rights. When the price of corn rises, workers’wages will rise, and conversely, when the price of corn decreases, workers’ wages will also decrease. Viewed from a fiqh perspective, as mentioned in surah Hud verse 6 “and there is no guarantee that there is not a single creeping animal on earth but Allah is the one who provides his sustenance” but that guarantee that there it is not given without effort as Allah has explained in surah Ar-Ra’d verse 11 “indeed Allah does not change the condition of a people until they change the condition of themselves”. From a jurisprudence perspective, the level of welfare of corn workers is not as significant due to the weakening corn princes in Sumbawa district.